Fair Talk: Moving Beyond the Conversation in Search of Increased and Better Feedback. Issue 10 (20th November 2017) - Lane, Angela M.; Gorbatov, Sergey
Abstract: At the junction of scientific research and practical experience, this article calls for attention to the topic of performance feedback. It clearly describes what good performance feedback is and analyzes the reasons why establishing feedback‐providing practices in modern organizations can be challenging. The authors suggest a simple three‐step model for giving fair performance feedback along with a series of steps leaders could take to become better at managing and developing their people. Organizational aspects of the role of feedback in talent management are also discussed.